Immediate Postpartum Hormonal Contraceptives and Their Association With Postpartum Depression [A12]. (May 2022) - Prasad, Shailly; Frid, Gabriela; Roig, Jacqueline; Lunde, Britt; Molenaar, Nina M.
Abstract : INTRODUCTION: The purpose of this study is to determine the association between immediate postpartum hormonal contraceptives and postpartum depression (PPD) as represented by the Edinburgh Postpartum Depression Score (EPDS). Immediate postpartum contraception, including long-acting reversible contraception (LARC) placement, is convenient, effective, and becoming more accessible given ongoing reimbursement changes. Some hormonal contraceptives have been suggested to cause mood changes outside of the peripartum period. However, they have not been fully studied in the postpartum period, and postpartum depression is a significant cause of morbidity post-delivery. METHODS: A retrospective cohort study was performed on patients presenting for their postpartum visit from January 1, 2016 through June 30, 2019 at a hospital-based outpatient clinic. Patients were divided into three study arms (1) hormonal contraceptive (2) non-hormonal contraceptive, and (3) no contraceptive. The primary outcome, EPDS score, was collected at the postpartum visit (4-10 weeks after delivery). Multivariate analysis was performed to control for confounders including multiparity, history of mood disorders and psychiatric medications, and neonatal outcomes. RESULTS: A total of 1, 041 patients were included in the analysis. The rate of immediate postpartum hormonal contraceptive use was 14.6%. There was no difference in the mean or median EPDS across the three study groups. There was not enough evidence to conclude that the rate of EPDS>12 or EPDS as a continuous variable was significantly different between the groups. CONCLUSION: Patients who received hormonal contraceptives were neither at increased risk nor decreased risk for postpartum depression.